The Effect of Parental and Grandparental Supervision Time Investment on Children's Early-Age Development - Stefani Milovanska-Farrington (Institute of Labor Economics (IZA), 2021)
This article explores the impact of grandparents' supervision time input relative to the effect of parents' childcare provision on children's cognitive, social and behavioral development at an early age. We identify the effects of interest through panel data estimation methods. The findings provide evidence of complementarity between parental and grandparental involvement in the child-rearing process. Specifically, grandparental care has a stronger effect than parental intervention on the vocabulary skills of the child. However, parents' time input in the child has a larger impact than does the supervision time investment of grandparents on the socio-behavioral development and the picture similarities measure of cognitive ability of children between 3 and 6 years old.
Keywords: J12; J13; J01; I21; I10; C33; 330; cognitive; behavioral; development; grandchildren; early age